2021
DOI: 10.3390/biomedicines9091242
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells as a Tool to Untangle the Breast Cancer Heterogeneity Issue

Abstract: Breast cancer (BC) is a disease characterized by high degrees of heterogeneity at morphologic, genomic, and genetic levels, even within the same tumor mass or among patients. As a consequence, different subpopulations coexist and less represented clones may have a selective advantage, significantly influencing the outcome of BC patients. Circulating tumor cells (CTCs) represent a rare population of cells with a crucial role in metastatic cascade, and in recent years have represented a fascinating alternative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Tools for stratifying patients and defining the real benefit of escalated treatments are needed to reduce unnecessary overtreatment and maximize the therapeutic effect. However, it is common to observe different transitional phenotypes and molecular heterogeneity derived from the epithelial to mesenchymal transition of CTCs in the bloodstream, limiting their applicability in clinical practice [76]. The molecular heterogeneity of CTCs may be more representative of the entire clones of metastatic BC, which is notoriously a heterogenous disease but is also present in the earlier stages [77].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Tools for stratifying patients and defining the real benefit of escalated treatments are needed to reduce unnecessary overtreatment and maximize the therapeutic effect. However, it is common to observe different transitional phenotypes and molecular heterogeneity derived from the epithelial to mesenchymal transition of CTCs in the bloodstream, limiting their applicability in clinical practice [76]. The molecular heterogeneity of CTCs may be more representative of the entire clones of metastatic BC, which is notoriously a heterogenous disease but is also present in the earlier stages [77].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…3) According to the report, 20-30% of BC patients may undergo metastasis after tumor resection and adjuvant therapy of the primary tumor. 4) Although researchers have made great strides in the treatment and diagnosis of BC, 5,6) BC is still a major health issue and currently represents a top biomedical research priority.…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent evidence suggests the feasibility for a CTC-driven treatment choice ( 12 ). To note, CellSearch is limited to EpCAM-positive cells, and several studies showed how downregulation of EpCAM and epithelial-mesenchymal transition occur often in cancer and might reduce detection rate ( 11 ). Indeed, several groups have reported about the presence of non-epithelial CTC and their correlation with worse prognosis and resistance to therapies ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several groups have reported about the presence of non-epithelial CTC and their correlation with worse prognosis and resistance to therapies ( 9 ). For this major drawback, new technologies for CTC enrichment and enumeration are under development, as for example size-based methods, which however are limited by a low specificity ( 11 ). Besides their clinical significance, CTCs isolation and characterization offer the opportunity for probing the biological evolution of cancer towards the metastatic stage ( 7 ).…”
Section: Introductionmentioning
confidence: 99%